Posttranslational generation of carboxylate ligands from aliphatic side chains in the photosynthetic oxygen-evolving complex - Hatsune Mizue; Takehiro Suzuki; Takumi Matsubara; Tomomi Kitajima-Ihara; Minako Hirano; Yuichiro Shimada; Yuki Kato; Naoshi Dohmae; Takumi Noguchi (Proceedings of the National Academy of Sciences, 2026)
Photosynthetic oxygen evolution is catalyzed by the Mn 4 CaO 5 cluster within the oxygen-evolving complex (OEC) of photosystem II (PSII). Although oxygenic photosynthesis likely arose before the Great Oxidation Event (~2.4 billion years ago), how the OEC emerged in ancestral PSII remains unresolved. We previously showed that cyanobacterial mutants in which Asp or Glu ligands of the Mn 4 CaO 5 cluster were replaced with His or Asn/Gln underwent posttranslational conversion back to the original carboxylate residues. Here, we examined whether aliphatic amino acids lacking reactive side chains can also undergo similar conversion, thereby testing the generality of this phenomenon. Mutations of D1-Asp170 to Val/Leu/Ile and of D1-Glu189 to Leu/Ile resulted in posttranslational generation of Asp/Glu or their derivatives, partially restoring O 2 -evolving activity. Notably, nonstandard Asp/Glu derivatives also appear capable of functioning as carboxylate ligands for the Mn 4 CaO 5 cluster. This transformation of aliphatic residues represents a distinct type of posttranslational modification. Together, these findings demonstrate that posttranslational generation of carboxylate ligands from diverse amino acid residues, including aliphatic side chains, is a general feature of the OEC. Such intrinsic chemical plasticity of the OEC supports the hypothesis that posttranslational amino acid conversion played a critical role in the origin and evolution of the OEC, enabling photosynthetic oxygen production that transformed Earth’s environment and promoted the evolution of life.